Integration von Sekundärdaten in die Nationale Diabetes-Surveillance: Hintergrund, Ziele und Ergebnisse des Sekundärdaten-Workshops am Robert Koch-Institut = Integration of secondary data into national diabetes surveillance: Background, aims and results of the secondary data workshop at the Robert Koch Institute - Schmidt, Christian; Laux, Gunter (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2017)
Epidemiological data provide evidence that diabetes mellitus is a highly relevant public health issue in Germany as in many other countries. The Robert Koch Institute (RKI) is in the process of building a national diabetes surveillance system that is aimed at establishing indicator-based public health monitoring of diabetes population dynamics using primary and secondary data. The purpose of the workshop was to conduct an inventory of available secondary data sources and to discuss data contents, data access, data analysis examples in addition to the options for ongoing data use for diabetes surveillance.